Evaluation of glove liners made of semipermeable and textile materials in patients with hand dermatoses: results of a multicenter intervention study (ProTection II) - Heichel, Theres; Kersten, Jan F.; Braumann, Antje; Krambeck, Kathrin; Bonness, Sonja; Schröder-Kraft, Claudia; Ofenloch, Robert; Weisshaar, Elke; Strom, Kerstin; Skudlik, Christoph; Sonsmann, Flora; Wilke, Annika; et al. (Contact dermatitis, 2025)
Background Glove liners (GLs) are worn under impermeable gloves to prevent occlusion effects. Objectives To evaluate the acceptance and tolerability of cotton gloves (COT) and semipermeable Sympatex gloves (SYM) as GLs in patients with hand dermatoses. Methods In a prospective multicenter study, 210 patients with work-related hand dermatoses were invited to wear either COT or SYM as GLs for 4 weeks underneath occlusive protective gloves during their regular work tasks. Acceptance of GL and health-related quality of life (HRQoL) were assessed by questionnaires and the disease severity by the Osnabrueck Hand Eczema Severity Index. Results A total of 178 data sets were available (SYM: n = 89/103, 86.4%; COT: n = 89/107, 83.2%). Both GLs did not impair work performance and were applicable in various work activities. SYM received better ratings regarding climate conditions, mobility and tactility. COT showed superiority in fit, donning and doffing. No substantial intergroup differences regarding disease severity and HRQoL were observed. Conclusions SYM and COT were well tolerated and accepted, suggesting that SYM is a reasonable alternative for COT as GL in patients with hand dermatoses. The choice of material of GLs may depend on occupation-specific requirements for the performed tasks, individual needs and preferences.